Tata Tertib Busana Kampus: Edukasi, Etika dan Komunikasi - Hayati, Afita Nur (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2013)
Education as consciuos process have prime goals, help youngers be smart and help them have morality. Therefore, they must study about ethics, a science that learn about bad and good manner as long as people’s knows through communications, a fundamental instrument to sharing meaning in order to have similarity namely religious culture.